Taxation and Labour Supply of Married Couples across Countries: A Macroeconomic Analysis - Bick, Alexander; Fuchs-Schündeln, Nicola (Review of Economic Studies, 2018)
We document contemporaneous differences in the aggregate labour supply of married couples across seventeen European countries and the U.S. Based on a model of joint household decision making, we quantify the contribution of international differences in non-linear labour income taxes and consumption taxes to the international differences in hours worked in the data. Through the lens of the model, taxes, together with wages and the educational composition, account for a significant part of the small differences in married men’s and the large differences in married women’s hours worked in the data. Taking the full non-linearities of labour income tax codes, including the tax treatment of married couples, into account is crucial for generating the low cross-country correlation between married men’s and women’s hours worked in the data, and for explaining the variation of married women’s hours worked across European countries.